An analysis of the relationship between the Chief Executive Officer's Gender and firm performance - Matsila, Siphiwa Lydia (University of Limpopo, 2016)
This paper evaluated the relationship between the Chief Executive Officer’s gender and firm performance. This study was conducted by evaluating the differential effect of CEO’s gender and sales turnover, share price and net profit. The study was deemed necessary because related researches in South Africa did not address the relationship between gender and variables such as turnover, share price and net profit. Hence this research focuses on the evaluation of the differential effect between CEO's gender and the corporate turnover, share price and net profit. The methodological approach used in this study was the quantitative approach. Data were collected from the archives of Socially Responsible Investing Index companies in the JSE. The T-test of difference was applied for data analysis of sixteen (16) selected companies. Three specific objectives were examined as follows: (1) To evaluate the relationship between the CEO's gender and company turnover (2) To assess the relationship, the CEO's gender and share price (3) To examine the relationship between the CEO's gender and net profit. Findings from the statistical analysis revealed that there is no significant relationship between CEO gender and sales turnover. It was further identified that no relationship exists between CEO gender and share price. It was also discovered that there is no differential effect between CEO gender and net profit. Findings from statistical analysis revealed that P-Value was greater than 5 percent indicating that there was no significant relationship between CEO gender and sales turnover, share price and net profit. This means that within the companies examined, CEO gender had no influence on sales turnover, share price and net profit. Based on the findings above, women CEOs can perform as well as the men CEOs. Therefore, women should be afforded the CEO’s positions as their presence have no negative effect on firm performance. Key words: CEO gender, firm performance, sales turnover, share price, net profit, JSE listed companies, corporate profitability, shareholder value and gender stereotyping.
Thesis (MBA.) -- University of Limpopo, 2016
Keywords: CEO gender; Firm performance; Sales turnover; Share price; Net profit; JSE listed companies; Corporate profitability; Shareholder value; Gender stereotype; Goal setting in personnel management; Performance - Management; Sex differences